Peranan Kepolisian dalam Menangani Tindak Pidana Pencurian Dengan Kekerasan di Polsek Gading Cempaka - Junior, Yohanes Putra; Anita, Fitri; Ependi, Ependi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The Gading Cempaka Police Station, as one of the police units in the area, has the main responsibility in handling various criminal cases, including theft with violence. The role and performance of the Police in handling this crime is crucial in an effort to create a safe and peaceful environment for the community. The problems that will be discussed in this study are: How is the role of the police in handling violent theft crimes at the Gading Cempaka Police and what are the obstacles in handling violent theft crimes at the Gading Cempaka Police. From the results of the research and discussion above, it can be concluded as follows: 1. The role of the police in handling violent theft crimes at the Gading Cempaka Police is by making preventive and repressive efforts. Preventive efforts by holding activities such as certain operations, selective raids, guarding, police patrols, and routine patrols. While the repressive efforts of the police take action together with the prosecutor's office and the court in imposing criminal sanctions. 2. The obstacles encountered in handling violent theft crimes at the Gading Cempaka Police are: a. The victim did not immediately report to the local police, so the role of the community in preventing and overcoming this crime is very much needed. b. It is difficult to find evidence. This extensive network of violent theft crimes makes it difficult for the authorities to conduct investigations and inquiries.